Who goes first? Strategic delay under information asymmetry - Peter A. Wagner (Theoretical Economics, 2018)
This paper considers a timing game in which heterogeneously informed agents have the option to delay an investment strategically to learn about its uncertain return from the experience of others. I study the effects of information exchange through strategic delay on long-run beliefs and outcomes. Investment decisions are delayed when the information structure prohibits informational cascades. When there is only moderate inequality in the distribution of information, equilibrium beliefs converge in the long run, and there is an insufficient aggregate investment relative to the efficient benchmark. When the distribution of information is more skewed, there can be a persistent wedge in posterior beliefs between well and poorly informed agents, because the poorly informed tend to "drive out" the well informed.
Keywords: D83; C73; 330; Strategic delay; social learning